Bispecific CAR-T cells targeting both CD19 and CD22 for therapy of adults with relapsed or refractory B cell acute lymphoblastic leukemia - Dai, Hanren; Wu, Zhiqiang; Jia, Hejin; Tong, Chuan; Guo, Yelei; Ti, Dongdong; Han, Xiao; Liu, Yang; Zhang, Wenying; Wang, Chunmeng; Zhang, Yajing; Chen, Meixia; et al. (Journal of hematology and oncology, 2020)
Despite the impressive complete remission (CR) induced by CD19 CAR-T cell therapy in B-ALL, the high rate of complete responses is sometimes limited by the emergence of CD19-negative leukemia. Bispecific CAR-modified T cells targeting both CD19 and CD22 may overcome the limitation of CD19-negative relapse. We here report the design of a bispecific CAR simultaneous targeting of CD19 and CD22. We performed a phase 1 trial of bispecific CAR T cell therapy in patients with relapsed/refractory precursor B-ALL at a dose that ranged from 1.7 × 10 to 3 × 10 CAR T cells per kilogram of body weight. We demonstrate bispecific CD19/CD22 CAR T cells could trigger robust cytolytic activity against target cells. MRD-negative CR was achieved in 6 out of 6 enrolled patients. Autologous CD19/CD22 CAR T cells proliferated in vivo and were detected in the blood, bone marrow, and cerebrospinal fluid. No neurotoxicity occurred in any of the 6 patients treated. Of note, one patient had a relapse with blast cells that no longer expressed CD19 and exhibited diminished CD22 site density approximately 5 months after treatment. In brief, autologous CD19/CD22 CAR T cell therapy is feasible and safe and mediates potent anti-leukemic activity in patients with relapsed/refractory B-ALL. Furthermore, the emergence of target antigen loss and expression downregulation highlights the critical need to anticipate antigen escape. Our study demonstrates the reliability of bispecific CD19/CD22 CAR T cell therapy in inducing remission in adult patients with relapsed/refractory B-ALL. ClinicalTrials.gov identifier: NCT03185494.